2014
DOI: 10.1007/s00044-014-1162-2
|View full text |Cite
|
Sign up to set email alerts
|

Multistep synthesis of 1-[{(5-alkenyl/hydroxyalkenylsubstituted)-1,3,4-oxadiazol-2-yl}-methyl]-2-methyl-1H-benzimidazole series and in vitro anticancer screening, SAR studies

Abstract: A novel series of hydroxy and non-hydroxy long chain substituted 1,3,4-oxadiazole moiety bearing 2-methyl-1H-benzimidazoles 15(a-d) have been synthesized from cyclization reaction of 2-(2-methyl-1H-benzimidazol-1-yl) acetohydrazide (13) with different unsaturated hydroxy and non-hydroxy fatty esters in the presence of phosphorus oxychloride and product obtained in appreciable yield. Compound (13) was synthesized from the corresponding ethyl (2-methyl-1H-benzimidazol-1-yl) acetate (12) and 2-methyl-1H-benzimida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Gurkan‐Alp et al reported a series of novel 2‐(4‐phenoxyphenyl)‐1 H ‐benzimidazole derivatives (Scheme ) of which compounds 570 , 571 and 574 exhibited remarkable cytotoxic activity. Varshney et al carried out the synthesis of novel series of hydroxyl and non‐hydroxy long chain substituted 1,3,4‐oxadiazole moiety bearing 2‐methyl‐1 H ‐benzimidazoles (Scheme ). Compounds 587a , c , d showed excellent anticancer activity against Hep3B, MCF7 and HeLa cell lines with IC 50 values of 11.10 ± 1.1, 12.40 ± 0.5, 11.70 ± 2.9 μM ( 587a ), 14.10 ± 0.8, 12.20 ± 0.7, 14.40 ± 1.2 μM ( 587c ) and 13.90 ± 0.8, 11.10 ± 0.7, 10.60 ± 1.2 μM ( 587d ) against doxorobucin and fluorouracil as the standard drugs.…”
Section: Pharmacological and Synthetic Profiles Of Benzimidazole Derimentioning
confidence: 99%
“…Gurkan‐Alp et al reported a series of novel 2‐(4‐phenoxyphenyl)‐1 H ‐benzimidazole derivatives (Scheme ) of which compounds 570 , 571 and 574 exhibited remarkable cytotoxic activity. Varshney et al carried out the synthesis of novel series of hydroxyl and non‐hydroxy long chain substituted 1,3,4‐oxadiazole moiety bearing 2‐methyl‐1 H ‐benzimidazoles (Scheme ). Compounds 587a , c , d showed excellent anticancer activity against Hep3B, MCF7 and HeLa cell lines with IC 50 values of 11.10 ± 1.1, 12.40 ± 0.5, 11.70 ± 2.9 μM ( 587a ), 14.10 ± 0.8, 12.20 ± 0.7, 14.40 ± 1.2 μM ( 587c ) and 13.90 ± 0.8, 11.10 ± 0.7, 10.60 ± 1.2 μM ( 587d ) against doxorobucin and fluorouracil as the standard drugs.…”
Section: Pharmacological and Synthetic Profiles Of Benzimidazole Derimentioning
confidence: 99%
“…In another study, compound 243 displayed most notable activity against HeLa cell lines (IC 50 = 05.34 ± 1.2 µM) compared to standards doxorubicin and 5-flurouracil (IC 50 = 03.56 ± 2.7 and 02.78 ± 2.6 µM, respectively). On the other hand, compound 244 showed marked activity against Hep3B cell line with an IC 50 value of 11.10 ± 1.1 µM ( Varshney et al, 2015 ).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Introduction of a purine moiety in benzimidazole derivative IV was found to exhibit growth inhibitory activity towards Aurora-A kinase with an IC 50 value of 10 nM [8]. Varshney et al investigated the multi-step synthesis of 1-[(5alkenyl/hydroxyalkenyl substituted-1,3,4-oxadiazol-2-yl)-methyl]-2-methyl-1H-benzimidazoles and found that compound V was the most bioactive benzimidazole derivative [9] against human breast adenocarcinoma (MCF-7 cell, IC 50 40 µM) and human cervical carcinoma (HeLa) cell lines (IC 50 5.3 µM). Introduction of a 4-amino-quinolyl fragment to benzimidazole at the C-4 position in compound VI exhibited inhibitory activity against VEGFR-2 (IC 50 = 30 nM) associated to anticancer activity against MCF-7 cancer cells (IC 50 = 1.3 µM) [10].…”
Section: Introductionmentioning
confidence: 99%